2019
DOI: 10.1016/j.reth.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of particle dispersion in the preprocessing stage for a static cell cultivation

Abstract: In order to produce high-quality cells in a static culture, the initial placement of the cells is one of the most important factors. Dense distribution of the cells increases the risk of cell death. Thus, the cells need to be uniformly distributed during the preprocessing of a static culture. This process depends on the operator's experience and has not been standardized. In this study, we have performed numerical simulations to investigate the efficiency of cell dispersion by using OpenFOAM. The numerical dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Nevertheless, these bioreactors hardly ful ll the demands of manufacturing, as they are associated with low e ciency, high local shear stress, and a lack of stringent quality control (Yamamoto et al, 2018;Kamao et al, 2014). Furthermore, a novel bioreactor with single-direction recip-rocal shaking (SRS) and multi-direction reciprocal shaking (MRS) was also investigated to optimize the dispersion of particles (Sekimoto et al, 2019). It was found that the MRS method exhibited an advantage for distributing particles when compared with the SRS method.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these bioreactors hardly ful ll the demands of manufacturing, as they are associated with low e ciency, high local shear stress, and a lack of stringent quality control (Yamamoto et al, 2018;Kamao et al, 2014). Furthermore, a novel bioreactor with single-direction recip-rocal shaking (SRS) and multi-direction reciprocal shaking (MRS) was also investigated to optimize the dispersion of particles (Sekimoto et al, 2019). It was found that the MRS method exhibited an advantage for distributing particles when compared with the SRS method.…”
Section: Introductionmentioning
confidence: 99%